A groupoid approach to C*-algebras associated with λ-graph systems and continuous orbit equivalence of subshifts. Issue 3 (2nd July 2020) - Matsumoto, Kengo
ABSTRACT: A λ -graph system L is a labelled Bratteli diagram with shift operation. It is a generalized notion of finite labelled graph and presents a subshift. We will study continuous orbit equivalence of one-sided subshifts and topological conjugacy of two-sided subshifts from the view points of groupoids and C ∗ -algebras constructed from λ -graph systems.